PENGARUH PEMBINAAN, LINGKUNGAN KERJA DAN KOMUNIKASI (STUDI KASUS PADA SMP NEGERI 2 KALIORI) - Kholifah, Siti Wahyu Iyatul; Nurhidayati, Anik (Potensio, 2013)
The research aims to test the effect of managemet development, working environment, and communication to employee performance. This research uses the entire population of the SMP Negeri 2 Kaliori as many as 37 people. Results of reserach refer that the managemet development have an influence positive but not significant to employee performance, while the working environment and the communication have an influence positive significant to employee performance. In addition, the results also refer that managemet development, work environment and communication have an influence positive significant together to employee performance.Key word: Managemet development, working environment, communication, employeeperformance